The Effect of Health Promotion Using E-Health Versus Lecture Toward Knowledge of Personal Hygiene Among Junior High School Students in Banten - Patonah, Ipat; Masluroh, Masluroh (STIKep PPNI Jawa Barat, 2024)
Aims: Knowing the effectiveness of health promotion between the e-health method and the lecture method on knowledge of personal hygiene external genitalia in junior high school students at Pondok Pesantren Latansa Lebak Banten. Method: The study involved 84 female students at SMP Pondok Pesantren Latansa Lebak Banten, using a quasi-experimental design, pretest-posttest, and control group design. Result: The results of univariate research on personal hygiene knowledge of external genitalia with health promotion e-health method obtained before that most were sufficient 47.6% and after most were good 71.4%. Knowledge of external genitalia personal hygiene with the lecture method health promotion was obtained before most of it was 50.0% and after most it was enough 52.4%. The bivariate results of the paired simple t test were 0.000 and the independent t test obtained a p value = 0.003. Conclusion: The e-health method is more effective in promoting knowledge of external genitalia personal hygiene among junior high school students than lecture methods, and cooperation with health workers is hoped to improve female students' hygiene practices